Ownership Concentration, Firm Size and Information Value Relevance: Indonesian Evidence - Krismiaji Krismiaji; Dwi Haryono Wiratno; Sidiq Ashari (Universitas Muhammadiyah Yogyakarta, Indonesia, 2019)
This paper describes empirical evidence investigated the effect of ownership concentration and firm’s size on the accounting information value relevance. Ownership concentration (OC) is measured by Herfindahl index; firm's size is measured by a log of total assets, whereas value relevance is measured by the Ohlson’ Price Model. Using a sample of 119 manufacturing firms listed in Indonesian Stock Exchange (IDX) for the year of 2011-2015, this research finds that ownership concentration positively affects both the value relevance of earnings per share and book value per share. Moreover, the firm's size negatively affects the value relevance of earnings per share and book value per share. This study contributes to the existing literature about value relevance of ownership concentration and value relevance of firm's size, especially in the post- IFRS adoption period.